Mindfulness in Motion and Dietary Approaches to Stop Hypertension (DASH) in Hypertensive African Americans. Issue 3 (23rd November 2020) - Wright, Kathy D.; Klatt, Maryanna D.; Adams, Ingrid Richards; Nguyen, Christopher M.; Mion, Lorraine C.; Tan, Alai; Monroe, Todd B.; Rose, Karen M.; Scharre, Douglas W.
Abstract : Objectives: Hypertension increases the risk of developing Alzheimer's disease or related dementias. This pilot study's purpose was to examine the feasibility and acceptability of a novel intervention, Mindfulness in Motion (MIM) and Dietary Approaches to Stop Hypertension DASH (MIM DASH), to improve diet, mindfulness, stress, and systolic blood pressure (BP) in older African Americans with mild cognitive impairment (MCI) and hypertension. Design: Cluster randomized controlled trial. Setting: Intergenerational community center in a large metropolitan area. Participants: African Americans with MCI and hypertension. Participants were divided into six groups randomized 1:1:1 to the MIM DASH group, attention only (non‐hypertensive education) group, or true control group. The MIM DASH and attention only interventions were delivered in 8‐weekly 2 hour group sessions. MIM included mindful movements from chair/standing, breathing exercises, and guided meditation. The DASH component used a critical thinking approach of problem solving, goal setting, reflection, and self‐efficacy. The true control group received a DASH pamphlet at the end. Measurements: Feasibility was tracked through enrollment and attendance records; acceptability was assessed through interviews. Blood pressure was measured using the Omron HEM‐907XL Monitor. Dietary intake was measured by DASH‐Q. Mindfulness was measured by the Cognitive and Affective Mindfulness Scale. Stress was measured by the Perceived Stress Scale. MCI was determined using the Self‐Administered Gerocognitive Examination. Data were collected at baseline and 3‐months. Results: Median session attendance was six for the MIM DASH group and six for the attention only group. There were no changes in diet, mindfulness, or stress. There was a clinically significant reduction in systolic BP in the MIM DASH group (−7.2 mmHg) relative to the attention only group (−.7), and no change between the MIM DASH and true control groups. Conclusion: Results indicate that the MIM DASH intervention was feasible and culturally acceptable in African Americans with hypertension and MCI.